PENINGKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVISME DI KELAS V SEKOLAH DASAR - Tin Indrawati (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
This study originated from the fact, in a study conducted Civics teacher is still confered on the teacher, not to put students as subjects that impact student learning tired, less motivated in learning the resulting lack of student learning outcomes. For that need a research aimed at improving student learning outcomes in learning through the use of Civics constructivism approach. The approach used in this study qualitative and quantitative approaches to the type of two cycles classroom action research. Implemented in class V with students 19 people. This study showed a increase in student learning outcomes from cycle I to cycle II of the cognitive (average 72 to 80), affective (an average of 70 to 77), psychomotor (on average 71 to 77).